PENGARUH KOMPETENSI DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL MEDIASI (Studi Pegawai Politeknik Ilmu Pelayaran ( PIP ) Semarang) - Adhi Prastistha Silen (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2016)
An organization would expect the productivity of its employees for the achievement of organizational goals. Work productivity is seen as the ability of employees to achieve the desired results, in achieving the desired results would require a positive work attitude of employees. Therefore it is expected for the organization must be aware and create a management system that takes into account the factors that affect the work attitude of employees in order to achieve the goals of the organization itself. The purpose of this study was to analyze the effect of competence and career development to organizational commitment in the EmployeeSeamanshipPolytechnicSemarang. To analyze the effect of competence, career development and organizational commitment to job satisfaction within the Employee Seamanship Polytechnic Semarang. To analyze the effect of competence and career development to job satisfaction and organizational commitment in environmental mediation Employee Seamanship Polytechnic Semarang.In this studytook thepopulationin this studywere employees ofthe PolytechnicSemarangSeamanship, amounting to 218 persons. Sampling with random samplingtechniquethatrandomlysampling142respondents. Keywords: competence, career development, organizational commitment and job satisfaction